2013
DOI: 10.1097/tp.0b013e3182a9274a
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii Serostatus Is Not Associated With Impaired Long-Term Survival after Heart Transplantation

Abstract: BackgroundConflicting data have been reported about the effect of Toxoplasma serostatus on mortality after heart transplantation. Either a positive or a negative recipient Toxoplasma serostatus was found to be associated with increased mortality.MethodsWe evaluated the effects of T. gondii infection on survival of our 582 cardiac allograft recipients operated upon between June 1984 and July 2011.ResultsThe 258 Toxoplasma seronegative and 324 seropositive recipients differed in age, pretransplantation diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
3
11
0
7
Order By: Relevance
“…Both CMV serology donor–recipient mismatch and the occurrence of CMV disease were not significantly different between the two cohorts. Furthermore, we previously established that the Toxoplasma gondii sero‐status was not associated with long‐term survival after HT .…”
Section: Resultsmentioning
confidence: 99%
“…Both CMV serology donor–recipient mismatch and the occurrence of CMV disease were not significantly different between the two cohorts. Furthermore, we previously established that the Toxoplasma gondii sero‐status was not associated with long‐term survival after HT .…”
Section: Resultsmentioning
confidence: 99%
“…At the time of the study, our results showed that none of our patients who received chemoprophylaxis with TMP/SMX developed T gondii infection. Although prophylactic antibiotic regimen is recommended for all patients who receive heart transplant, it could negatively affect the patient's outcome by its side effects 16 . There are some alternatives for TMP/SMX such as pyrimethamine‐sulphadoxine which is preferred in some centers as it can be administered weekly.…”
Section: Discussionmentioning
confidence: 99%
“…reviewed their experience at Erasmus Medical Center in The Netherlands of the 582 heart transplant recipients transplanted between the inception of the program in 1986 and 2011 (1). With a median follow-up of 8.3 years, the authors demonstrate that Toxoplasma-seronegative recipients had mortality rate of 35% compared with 65% for Toxoplasmaseropositive recipients.…”
mentioning
confidence: 93%